SOCIALLY SIGNIFICANT LIVER DISEASES AMONG THE ELDERLY POPULATION IN THE CONDITIONS OF THE ANDIJAN REGION (BASED ON THE RESULTS OF A 21-YEAR POPULATIONEPIDEMIOLOGICAL STUDY, GENDER CHARACTERISTICS) - N.S. Mamasoliev; N.S. Khakimov; D.M. Kalandarov; O.T. Umrzakov; K.Z. Kadirov (Scholar Express Journals, 2023)
Socially significant diseases of the liver, such as chronic hepatitis and cirrhosis of the liver, lead to the formation of structurally abnormal areas in the liver and cause irreversible changes, accompanied by a violation of the architecture of the liver. According to WHOSIS (2008), the incidence of liver cirrhosis in the world is recognized as 20-40 patients per hundred thousand of the population, and its prevalence, according to the results obtained by researchers, is steadily increasing. The contribution of liver cirrhosis caused by chronic hepatitis V, C, V+D, viral etiology, is 10-23.5% of all cirrhosis.
Keywords: Chronic hepatitis; liver cirrhosis